IMPROVING STUDENTS' AUTONOMOUS WORK AT THE DEPARTMENT OF NERVOUS DISEASES WITH NEUROSURGERY AND MEDICAL GENETICS BY USAGE OF INNOVATIVE TECHNOLOGIES - N.V. Lytvynenko; H.Ya. Sylenko; V.A. Pinchuk; T.Yo. Purdenko; V.M. Hladka; Yu.I. Sylenko (Ukrainian Medical Stomatological Academy, 2017)
The foreground aim of medical education and the criterion of its effectiveness become the development of personal potential and implementation of professional component of the doctor to-be. The relevance of the issue is to acquire the methods of autonomous cognitive activity determined by the fact that during the period of study at the university, the foundation for future independent professional activity is created. The aim of the study is to implement the innovative technologies for students' autonomous work at the Department of Nervous Diseases with Neurosurgery and Medical Genetics in order to improve the development of theoretical material and practical skills. Students' autonomous work during classes includes activities at lectures and practical exercises that vary for instance: "brainstorm", debate, discussions of specific situations etc. Students' autonomous work after classes includes the study of literature occupational edition, referencing literature, annotated books, articles, review the developed theoretical material, exercises, problem solving, preparing the reports, and autonomous work on the Internet (search for information on-line, organization of the dialogues online, creating thematic web-pages and web-quests). Another option in the process of students' autonomous work at the Department of Nervous Diseases with Neurosurgery and Medical Genetics, is the educational module aimed on independent supervision of patients followed by the writing of academic case histories. The distance education technologies are of great interest over the world nowadays, which is particularly important in higher and post-graduate education. Such learning method is provided by the development of telecommunication systems and the Internet. With the aim of self-study of the discipline at the Department, the video films and video clips about nosology, electronic stands of topical diagnosis were developed. Students are provided with the opportunity to work at the electronic library of the Academy, which stores a large number of textbooks, monographs, manuals, educational videos, and research papers on the most difficult topics of neuroscience. A large amount of educational material is presented on the website of the Academy. The students who are the most interested in learning are able to attend students' scientific group, meetings are held twice a month on different subjects aimed at in-depth study of neurology and acquiring and development of practical skills. At the end of academic year, some of them demonstrate research reports at students' conference according to the topics which they have chosen and have been working on with their scientific supervisors, while the rest of students publish the theses only. The Department of Nervous Diseases with Neurosurgery and Medical Genetics of Higher State Educational Establishment of Ukraine "Ukrainian Medical Stomatological Academy" creates adequate conditions for students' autonomous work so that young neurologists to-be could confidently pursue their profession thanks to the skills and abilities which they have obtained during the educational process.